Core–shell and alloy integrating PdAu bimetallic nanoplates on reduced graphene oxide for efficient and stable hydrogen evolution catalysts. Issue 69 (7th September 2017) - Jiang, Yi; Yan, Yucong; Han, Yu; Zhang, Hui; Yang, Deren
Abstract : PdAu nanoplates with different core–shell structures on rGO were generated by manipulating the competition between galvanic replacement and chemical reduction with the alloy and core–shell integrating nanoplates exhibiting superior HER properties. Abstract : PdAu bimetallic nanoplates are synthesized by titrating HAuCl4 into an aqueous solution containing in situ generated Pd square nanoplates (PdSPs) on reduced graphene oxide (rGO) in the presence of ascorbic acid (AA), serving as a reducing agent, at different injection rates. At a high injection rate ( e.g., 45 mL min −1 ), PdAu core–shell nanoplates on rGO are generated by strong galvanic replacement between PdSPs and the Au precursor, followed by reduction of the Pd precursor. In contrast, PdAu nanoplates with a core–shell and alloy integrating structure are obtained on rGO by co-reduction of the Au and Pd precursors by AA due to the inhibition of the abovementioned galvanic replacement at a slow injection rate ( e.g., 0.5 mL min −1 ). The PdAu nanoplates with a core–shell and alloy integrating structure on rGO exhibit a substantially enhanced catalytic activity towards the hydrogen evolution reaction (HER) relative to the PdAu core–shell nanoplates and PdSPs on rGO, and is comparable to the commercial Pt/C. Significantly, these core–shell and alloy integrating nanoplates on rGO have much superior durability over Pt/C for catalyzing the HER under acidic conditions. The remarkable enhancement in activity and durability can be attributed to the cooperative function of the PdAu alloy and electron coupling between nanoplates and graphene.